APPLICATION OF HUMAN RESOURCES MANAGEMENT ON UNCERTIFIED CONSTRUCTION LABOR - Ellin Herlina (Jurnal Ilmiah Hospitality, 2022)
Of the 8,300,000 construction workers, there are 7,684,000 who have not been certified. The solution that can be offered to bring the skills of non-certified workers closer to certified ones can be done by implementing Human Resource Management (HRM) for these construction workers. This study measures whether the application of HRM can perform this role. To measure each indicator, the Z test is carried out. The results show that there are several indicators that have a negative Z value, consisting of legal certainty from the government, construction actors can meet the demands of the development of the construction industry, are able to provide social protection for workers in the implementation of construction services and every uncertified construction worker who follows the flow of HRM implementation is entitled to appropriate compensation for the services provided. The Z count is positive but still below the table Z value is found in indicators of stakeholder readiness in implementing HRM, infrastructure readiness in implementing HRM, non-certified construction workers can meet international construction standards. The Z value in this indicator indicates that the implementation of HRM for uncertified workers effectively replaces certification but is not significant. The positive Z count above the Z table value is found in the indicator of the readiness of construction workers who are not certified following the implementation of HRM, construction actors are able to build quality education and job training institutions, construction actors can meet the needs of good governance, construction actors can meet governance needs good management, uncertified construction workers can meet national construction standards, uncertified construction workers are able to be professionally responsible for the results of their work. This third category indicates that the application of HRM to non-certified workers effectively replaces certification and is significant